Hubungan Nilai PPLK Dan Tingkat Pendidikan Orang Tua Dengan Minat Menjadi Guru Pada Mahasiswa Pendidikan Ekonomi Angakatan 2015 FE UNP - Sari Hayati Martin; Z Mawardi Efendi (Universitas Negeri Padang, 2020)
The study aims to find out: (1) The relationship between PPLK scores and the interest in becoming a teacher, (2) The relationship between parents’ level of education with the interest in becoming a teacher, (3) the relationship of PPLK scores eith the level of parent’s education level are factors that influence students’ interest to become teachers. This can be seen from the value of PPLK obtained by students which is very satisfying and supported by a good educational background of parents, so the interest of students to become teachers will be good too. This type of research is correlational. From the results of this analysis it can be concluded that: (1) there is no significant relationship between PPLK scores and the interest in becoming a teacher in terms of sig. 0,223>0,05. (2) there is a negative and insignificant relationship between the level of education of parents and the interest in becoming a teacher in the 2015 economic education student FE UNP as seen from the Sig. 0,482> 0,05 and pearson correlation values of -0,074. (3) there is no significant relationship between PPLK scores with parents’ education level seen from the Sig. value of 0,884>0,05.Keywords : PPLK value, parental education level, interest in becoming a teacher